2022
DOI: 10.3389/fnins.2021.773404
|View full text |Cite
|
Sign up to set email alerts
|

Development and Clinical Application of Positron Emission Tomography Imaging Agents for Monoamine Oxidase B

Abstract: Monoamine oxidase B (MAO-B) is a high-density protein in the brain mainly found on outer mitochondrial membranes, primarily in astroglia, but additionally in serotonergic neurons and in the substantia nigra in the midbrain. It is an enzyme that participates in the oxidative metabolism of important monoamines including dopamine, norepinephrine, benzylamine, and phenylethylamine. Elevated MAO-B density may be associated with astrogliosis and inhibiting MAO-B may reduce astrogliosis. MAO-B density is elevated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 73 publications
0
11
0
2
Order By: Relevance
“…[38][39][40][41] While there are no microglia-specific radioligands, there are radioligands that are more specific for astrocytes (radioligand [11C]-L-deprenyl-D2 targets the astrocyte-specific monoamine oxidase B). 42 An interesting PET study examining fibromyalgia patients observed elevated TSPO but not [11C]-L-deprenyl-D2 signals in the frontal and parietal lobes, supporting that microglia, but not astrocytes, contribute to neuroinflammation in these patients. 43 The development of more specific PET tracers for microglia (such as targeting other receptors like P2X purinoreceptor 7; P2XR7) and tracers capable of differentiating between microglia phenotypes will help advance our clinical understanding of the dynamics of microglial activation in pain and in other neurologic diseases.…”
Section: Neuroimmune Interfaces Within the Central Nervous Systemmentioning
confidence: 94%
See 2 more Smart Citations
“…[38][39][40][41] While there are no microglia-specific radioligands, there are radioligands that are more specific for astrocytes (radioligand [11C]-L-deprenyl-D2 targets the astrocyte-specific monoamine oxidase B). 42 An interesting PET study examining fibromyalgia patients observed elevated TSPO but not [11C]-L-deprenyl-D2 signals in the frontal and parietal lobes, supporting that microglia, but not astrocytes, contribute to neuroinflammation in these patients. 43 The development of more specific PET tracers for microglia (such as targeting other receptors like P2X purinoreceptor 7; P2XR7) and tracers capable of differentiating between microglia phenotypes will help advance our clinical understanding of the dynamics of microglial activation in pain and in other neurologic diseases.…”
Section: Neuroimmune Interfaces Within the Central Nervous Systemmentioning
confidence: 94%
“… 105 The PET tracer targeting TSPO, as discussed previously, cannot distinguish between microglia and astrocytic activity, but the tracer ligand [11C]-L-deprenyl-D2 is generally accepted for the detection of astrocytes due to the selective expression of its monoamine oxidase B target. 42 , 106–108 …”
Section: Neuroimmune Interfaces Within the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Der erste PET-Tracer war [ 11 C]Deprenyl, jedoch hat das hohe Hintergrundsignal aufgrund irreversibler Bindung und radioaktiver Metaboliten im gesunden Gehirn die Anwendbarkeit deutlich eingeschränkt. Neuere Studien verwenden daher reversible und selektive MAO-B Liganden wie das deuterierte [ 11 C]deuterium-L-Deprenyl, welches vielversprechende Ergebnisse zeigt [13]. Bisherige Studien weisen darauf hin, dass das Level der Astrogliose mit der bisherigen Krankheitsdauer bei neuropsychiatrischen Erkrankungen wie z.…”
Section: Mao-bunclassified
“…Bisherige Studien weisen darauf hin, dass das Level der Astrogliose mit der bisherigen Krankheitsdauer bei neuropsychiatrischen Erkrankungen wie z. B. Depression korreliert, was den Anstieg der Astrogliose im Krankheitsverlauf widerspiegeln würde [13]. Die MAO-B-PET wird derzeit noch nicht regulär in der klinischen Routine angewendet, sondern lediglich in wissenschaftlichen Studien evaluiert.…”
Section: Mao-bunclassified